Response of Hirayama disease to surgical intervention: case report - Kumar, Navneet; Mukherjee, Sumedha; Patel, Mukesh P.; Shah, K. B.; Kumar, Sunil (International Journal of Research in Medical Sciences, 2017)
Hirayama disease also known as monomelic amyotrophy, primarily involves distal upper limb extremities.It differs from the known types of motor neuron diseases because of its nonprogressive behavior and pathologic findings of focal ischemic changes in the anterior horn of the lower cervical cord. We present a young male with Hirayama disease who had a left upper extremity involvement which was progressive in nature. He didn’t respond with initial treatment of cervical collar. Consequently surgical intervention improves muscle weakness and decrease the neurological deficit.